2009
DOI: 10.1007/s10457-009-9221-2
|View full text |Cite
|
Sign up to set email alerts
|

Coppicing improved fallows are profitable for maize production in striga infested soils of western Kenya

Abstract: Striga hermonthica (striga) weed is a major threat to crop production in sub-Saharan Africa, and short duration improved fallow species have recently been found to reduce the effects of this weed because of their ability to replenish soil nitrogen. The objective of this study was to compare the efficacy and profitability of coppicing improved fallow species (Gliricidia sepium [gliricidia], Leucaena trichandra [leucaena] and Calliandra calothyrsus [calliandra]) and non-coppicing species (Sesbania sesban [sesban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Improved tree fallows do provide substantial GWP offsets through the higher C stocks from AGB compared to baseline and the other scenarios. The food production component of improved fallows might be increased by increasing the length of the cropping relative to that of the fallow phase; time-averaged yields have been higher than unfertilized controls even when tree fallows are shortened to 7 months in higher rainfall areas such as Sauri (21). The benefits of higher yields would have to be weighed against reduced mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Improved tree fallows do provide substantial GWP offsets through the higher C stocks from AGB compared to baseline and the other scenarios. The food production component of improved fallows might be increased by increasing the length of the cropping relative to that of the fallow phase; time-averaged yields have been higher than unfertilized controls even when tree fallows are shortened to 7 months in higher rainfall areas such as Sauri (21). The benefits of higher yields would have to be weighed against reduced mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, Velvet bean and cowpea have already shown to reduce Striga spp. problems (Oswald et al, 2002;van Mourik et al, 2008;Kiwia et al, 2009). Based on agronomic reasons (e.g.…”
Section: Experimental Treatments and Plant Materialsmentioning
confidence: 99%
“…The latter has a positive effect on the rate of deforestation of the natural "miombo" woodland in some countries. Field studies in Kenya have demonstrated that agroforestry-based practices provide good weed control against Striga, a noxious weed due to the high contents of N added in the soil by the tree legumes species (Kiwia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%